Species richness and biomass of understory vegetation in a Eucalyptus globulus Labill. coppice as affected by slash management - Fabião, António (2007)
The aim of this study was to assess the effect of different slash management practices on understory biodiversity and biomass in Eucalyptus globulus coppices in Central Portugal. The experiment consisted of four treatments: (a) removal of slash (R), (b) broadcast over the soil (S), (c) as in S but concentrating woody residues between tree rows (W) and (d) incorporation of slash into soil by harrowing (I). Understory vegetation was surveyed during 1–6, 9, and 10 years, the proportion of soil cover by plant species estimated, and diversity and equitability indexes determined. Above ground understory biomass was sampled in years 2–6, 9, and 10. The highest number of species in most years occurred in plots where slash was removed. Differences between treatments in the proportion of plant soil cover were never significant, whereas differences in diversity index were only occasionally significant and apparently related to the number of species. Thus, differences in the equitability index were not significant. Understory biomass did not decrease during the rotation period, and was usually highest in R and I, and lowest in S, but not significantly different. At the end of the rotation period, understory biodiversity indices and biomass were apparently independent of slash treatment.